Efektivitas Akupresur P6 Terhadap Mual dan Muntah pada Hiperemesis Gravidarum - Dewi, Shofia; Sumaryani, Sri; Jumiyati, Endang (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Hyperemesis gravidarum is a condition characterized by excessive nausea and vomiting during the first trimester of pregnancy, which may lead to dehydration, electrolyte imbalance, and nutritional deficiencies affecting maternal and fetal health. Management of this condition is not limited to pharmacological therapy but may also involve non-pharmacological approaches, such as acupressure at the Pericardium 6 (P6) point. This study aimed to determine the effectiveness of P6 acupressure in reducing the severity of nausea and vomiting in pregnant women with hyperemesis gravidarum. This study used a descriptive case study design involving three first-trimester pregnant women with hyperemesis gravidarum. The P6 acupressure intervention was applied manually for 10 minutes per session and administered three times daily in the morning, afternoon, and evening. The severity of nausea and vomiting was measured using the Pregnancy-Unique Quantification of Emesis and Nausea (PUQE) instrument before and after the intervention. The results showed that all participants experienced a decrease in PUQE scores, with an average reduction of 2.1 points. This reduction indicated decreased nausea intensity and vomiting frequency. In addition, participants reported improved comfort and increased ability to consume food and fluids. No significant side effects were observed. P6 acupressure is an effective, safe, and easily applicable complementary therapy to reduce hyperemesis gravidarum symptoms in first-trimester pregnant women